(untitled) (American Journal of Islam and Society, 2014)
The Gezi Park protests have stirred serious controversy both inside and outside Turkey on the JDP’s ruling style and ideology. By drawing on el-Affendi’s distinction between the Medina and Damascus models, I discuss the Islamist opposition to Erdoğan during the Gezi events. I argue that notwithstanding his recent Islamization policies, Erdoğan’s JDP is a conservative party that caters to Muslim nationalism while a new Islamism as an ethico-political ideal has been in the making by the praxis of the new Islamist youth.